Pengaruh Pembiasaan Tilawah Al-Qur’an Terhadap Pembentukan Karakter Siswa - Redmon Windu Gumati (FKIP, Universitas Billfath Lamongan, 2020)
This research is motivated by reading the koran is an obligation that we must do as Muslim. However, unfortunately in this modern era and technologi Cellphones, Television, and Gadget have become an options to spend hours instead of having to spend a few minutes reading the koran. Therefore, habituation reding the koran are applied in schools is one of the activities has a positive impact on the formation of student character. The purpose of this study was`to determine the influence of habituation reading the koran on the formation of student character. The research method uses descriftive quantitative research methods, namely the research method used to exsamine thing that occur in the field, to provide a systematic and logical picture according to actual facts with certain population characteristics, and to provide and idea that this study is designed to obtain information about the deccription of the phenomenon of the vareables under study, therefore Researchers are required to go directly to the field. In this study, the validity and reliability of the instrument were tested using the pearson product moment and cronbach alpha formulas, the prerequisite analysis consisted of linearity testing, and hypothesis testing using regression correlation analysis with a significance level of 5%. By using documentation and questionnaire data collection techniques, from a sample of 83 students, the research results showed that the influence of al-Qur'an recitation habituation on the formation of student character. This is indicated by the correlation value (r) = 54.5% and from the results of the regression analysis with the t test it is obtained t count > t table or 5.843 > 1.664 (hypothesis H1 is accepted). The amount of contribution to the habituation of reading the koran recitations that can affect the character building of students is 29.7%, and the remaining 70.3% is by other factors.